Examining local perspectives on the influence of climate change on the health of Hamer pastoralists and their livestock in Ethiopia - Lumborg, S.; Tefera, S.; Munslow, B.; Mor, Siobhan M. (Springer, 2021)
This study explores the perceived influence of climate change on the health of Hamer pastoralists and their livestock in south-western Ethiopia. A combination of focus group discussions and key informant interviews were conducted with Hamer communities as well as local health workers, animal health workers and non-governmental organisation (NGO) staff. Thematic framework analysis was used to analyse the data. Reductions in rangeland, erratic rainfall, recurrent droughts and loss of seasonality were perceived to be the biggest climate challenges influencing the health and livelihoods of the Hamer. Communities were travelling greater distances to access sufficient grazing lands, and this was leading to livestock deaths and increases in ethnic violence. Reductions in suitable rangeland were also precipitating disease outbreaks in animals due to increased mixing of different herds. Negative health impacts in the community stemmed indirectly from decreases in livestock production, uncertain crop harvests and increased water scarcity. The remoteness of grazing lands has resulted in decreased availability of animal milk, contributing to malnutrition in vulnerable groups, including children. Water scarcity in the region has led to utilisation of unsafe water sources resulting in diarrhoeal illnesses. Further, seasonal shifts in climate-sensitive diseases such as malaria were also acknowledged. Poorly resourced healthcare facilities with limited accessibility combined with an absence of health education has amplified the community’s vulnerability to health challenges. The resilience and ambition for livelihood diversification amongst the Hamer was evident. The introduction of camels, increase in permanent settlements and new commercial ideas were transforming their livelihood strategies. However, the Hamer lack a voice to express their perspectives, challenges and ambitions. There needs to be collaborative dynamic dialogue between pastoral communities and the policy-makers to drive sustainable development in the area without compromising the values, traditions and knowledge of the pastoralists.